Sistem Pendukung Keputusan Pengangkatan Jabatan Karyawan pada PT.Ayn dengan Metode Profile Matching - Deny Adhar (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2014)
Career management employees a clear and transparent is one of the important factors that can improve the working atmosphere of harmony and deepen the level of trust between employees and management. The problem that often occurs in the employee performance appraisal process include the subjectivity of decision-making, especially when some employees have capabilities that are not much different. Decision Support Systems employee appointments is a system that is able to improve the effectiveness and efficiency of management as well as decisions that can provide performance evaluation of employees who will be promoted. Speed and validity in information processing mentioned above is the main requirement to support hiring decisions, so the decision support system used must also have a comprehensive and integrated plan to shrink the level of risk of failure of development and selection decisions, this study discusses the analysis of Aspects of Intellectual Capacity , Aspects of Work Attitude and Behavior Aspects categorized in the core factor and the secondary factor method combined with the GAP Analysis Profile Matching method. The results of the study in the form of a decision support system that can provide a performance evaluation of employees who will be promoted.